Water electrolysis hydrogen production membrane electrode and preparation method thereof
By combining thermal voltage transfer and spraying method in the membrane electrode to form a catalytic layer of a layered structure, the performance decline of the existing membrane electrode catalytic layer on the surface of the surface of the existing membrane electrode catalytic layer or the uneven structure of the uniform structure has achieved more efficient The electrolytic hydrogen process.
Patent Information
- Application Number
- CN202411559068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
There is a dense ionomer layer or an uneven structure on the surface of the existing membrane electrode catalytic layer, which leads to a degradation of the membrane electrode performance and limits the commercial application of electrolytic hydrogen production.
The method of combining thermal voltage transfer and spraying method is used to form a dense bottom catalytic layer on the proton exchange membrane through the thermal voltage transmission film, and then add a fluffy layer of the layer of the layered structure through the spray method to form the membrane electrode of a layered structure.
Through the layered membrane electrode design, Ohm losses and transmission loss are reduced, the performance and energy utilization efficiency of the membrane electrode is improved, and the energy consumption of the electrolyte is reduced.
Smart Images

Figure CN119372690A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a water electrolysis hydrogen production membrane electrode and a preparation method thereof, and in particular to a water electrolysis hydrogen production membrane electrode with a layered catalytic layer structure and a preparation method thereof. Background Art
[0002] Proton exchange membrane electrolyzer is an important electrochemical device that converts electrical energy into chemical energy. Figure 1 As shown in FIG. 1 , it is mainly composed of a membrane electrode 1 for producing hydrogen by electrolysis of water, a gas diffusion layer 2 (such as a titanium porous diffusion layer) and a bipolar plate 3, and is used for applications such as producing hydrogen by electrolysis of water. The membrane electrode is the core component of the proton exchange membrane electrolyzer and determines the energy utilization efficiency and energy consumption of the proton exchange membrane electrolyzer. The basic structure of the membrane electrode is shown in FIG. Figure 2 As shown, it is mainly composed of an anode 12, a cathode 13 and a proton exchange membrane 11, wherein the anode and the cathode are respectively located on both sides of the proton exchange membrane 11 and are in close contact with it. The anode 12 and the cathode 13 are usually covered with a noble metal catalyst layer, such as platinum and iridium, to promote the dissociation of water and the production of hydrogen / oxygen.
[0003] The catalyst layer of the membrane electrode is usually prepared by hot pressing transfer or spraying. In both methods, the catalyst and alcohol solvent are prepared into a slurry, and the slurry is deposited on the proton exchange membrane as a catalytic layer by hot pressing transfer or spraying. However, the catalytic layer structures prepared by these two methods have certain defects. The hot pressing transfer method transfers the catalytic layer pre-deposited on the Teflon membrane to the proton exchange membrane by heating and pressure. Due to the effects of heat and pressure, the catalytic layer structure of the membrane electrode prepared by this method is more dense and flat, which is conducive to the conductive contact between the catalytic layer and the titanium porous diffusion layer. However, this method will also reshape the structure of the catalytic layer due to the effects of heat and pressure, so that a dense ionomer layer is formed on the surface of the catalytic layer, which is not conducive to the transmission of oxygen bubbles generated by internal electrolysis, thereby reducing the performance of the membrane electrode. The spraying method is to spray the catalyst slurry directly onto the proton exchange membrane to deposit it as a catalytic layer. The prepared catalytic layer structure is more fluffy, and it is not easy to form a dense ionomer layer on the surface, which is conducive to the transmission of oxygen bubbles. However, the direct contact between the alcohol solvent in the catalyst slurry and the proton exchange membrane causes the proton exchange membrane to deform, resulting in an unevenly distributed catalytic layer structure, which is not conducive to the conductive contact between the catalytic layer and the titanium porous diffusion layer, thereby reducing the membrane electrode performance.
[0004] Patent application CN115125549A discloses a method for preparing a low-iridium membrane electrode for hydrogen production by electrolysis of water. By using a loaded one-dimensional ordered array low-iridium membrane electrode ordered structure, the polarization effect of mass transfer can be reduced, and water molecules, electrons and heat can be effectively transferred, thereby increasing the three-phase contact interface area between the precious metal catalyst, the carrier and water, improving the performance of the precious metal, reducing the amount of precious metal, and increasing the utilization rate of the precious metal. The preparation process first grows the catalyst on a hard titanium plate, adding an additional process. On the one hand, its cost is significantly increased, and on the other hand, this complex process is not conducive to the mass production of membrane electrodes. In addition, the preparation method still uses a hot pressing transfer method to prepare the surface catalytic layer, and mass transfer polarization will still occur due to the presence of a dense ionomer layer on the surface, resulting in a decrease in performance.
[0005] Patent application CN116936888A discloses an asymmetric integrated gas diffusion membrane electrode and a preparation method thereof, wherein the preparation method of the membrane electrode comprises the following steps: coating a layer of perfluorosulfonic acid solution on a substrate, and then covering the catalytic layer of the gas diffusion electrode on the upper surface of the perfluorosulfonic acid solution, and obtaining component A after heat treatment; depositing a catalyst on the membrane side of component A to prepare an asymmetric integrated membrane electrode. The membrane electrode has high durability and stability, and the preparation method is simple and convenient. However, the membrane electrode directly deposits the catalyst on the proton exchange membrane, which will result in greater proton transmission resistance, which in turn will increase the ohmic polarization of the membrane electrode and reduce performance.
[0006] In summary, the existing membrane electrode has the following technical problems: the dense ionomer layer on the surface of the membrane electrode catalyst layer or the uneven structure on the surface of the membrane electrode catalyst layer leads to reduced membrane electrode performance, which seriously limits the commercial application of membrane electrode electrolysis to produce hydrogen. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a water electrolysis hydrogen production membrane electrode and a preparation method thereof, so as to reduce the activation loss, ohmic loss and transmission loss of the electrode.
[0008] The purpose of the present invention can be achieved through the following technical scheme: a method for preparing a membrane electrode for hydrogen production by electrolysis of water, which method first transfers part of the catalyst layer slurry onto a proton exchange membrane by hot pressing to obtain a dense and flat bottom catalyst layer, and then sprays the remaining catalyst layer slurry thereon by spraying to obtain a layered membrane electrode.
[0009] Furthermore, the catalyst layer slurry comprises a catalyst, a perfluorosulfonic acid ionomer and a solvent in a mass ratio of 1:(0.1-1):(40-60), and the mass ratio of the catalyst, the perfluorosulfonic acid ionomer and the solvent is preferably 1:(0.2-0.4):(45-55), and further preferably 1:0.3:50.
[0010] Furthermore, the catalyst layer slurry is obtained by mixing the catalyst, the perfluorosulfonic acid ionomer and the solvent and dispersing them ultrasonically.
[0011] Furthermore, the perfluorosulfonic acid ionomer is Or other perfluorosulfonic acid ionomers, the solvent is ethanol or isopropanol. The anode catalyst layer and cathode catalyst layer of the layered structure are respectively arranged on both sides of the proton exchange membrane, wherein the catalyst used in the anode catalyst layer slurry is iridium dioxide or iridium black catalyst, and the catalyst used in the cathode catalyst layer slurry is platinum catalyst.
[0012] Furthermore, the specific steps of the hot pressing transfer are: depositing the catalyst layer slurry on the substrate by ultrasonic spraying or scraping to obtain a hot pressed sheet, and then covering the obtained hot pressed sheet on the surface of the perfluorosulfonic acid proton exchange membrane, hot pressing, and then removing the substrate to obtain a membrane electrode with a dense bottom catalytic layer.
[0013] Furthermore, the substrate is a Teflon film substrate;
[0014] The hot pressing pressure is 0.1-1MPa, preferably 0.4-0.6MPa, more preferably 0.5MPa, the hot pressing temperature is 100℃-150℃, preferably 110℃-130℃, more preferably 120℃, and the hot pressing time is 1-10min, preferably 2-4min, more preferably 3min.
[0015] Furthermore, the pressure and temperature of hot pressing are used to regulate the flatness and density of the underlying dense layer, and the flatness and density of the underlying dense layer depend on the catalyst loading of the membrane electrode.
[0016] Furthermore, the catalyst layer slurry is divided into two parts, one of which accounts for 40-60% (preferably 50%) of the total weight of the catalyst layer slurry and is transferred on the proton exchange membrane by hot pressing, and the remaining part is loaded on the surface of the catalyst layer obtained by hot pressing transfer by spraying.
[0017] Furthermore, the usage ratio of the two catalyst layer slurries determines the thickness of the bottom dense layer of the membrane electrode, and the thickness of the bottom dense layer depends on the catalyst loading of the membrane electrode.
[0018] The invention also provides a water electrolysis hydrogen production membrane electrode prepared by the preparation method.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The present invention combines the spraying method and the hot pressing transfer method. First, a dense and flat bottom catalyst layer is obtained on the proton exchange membrane by hot pressing transfer, and then the slurry is sprayed thereon by the spraying method. In this way, the alcohol solvent in the slurry will not directly contact the proton exchange membrane during spraying to cause deformation of the membrane, and a loose and flat surface structure without a dense ionomer layer on the surface can be obtained. Such a layered membrane electrode design avoids the shortcomings of both the hot pressing method and the spraying method, and utilizes their advantages. On the one hand, the flat surface can enhance the conductive contact between the anode catalyst layer and the titanium porous diffusion layer to reduce ohmic losses. On the other hand, the porous and fluffy catalyst layer can also facilitate the oxygen bubbles generated in the anode catalyst layer during the electrolysis process to leave the catalyst layer to reduce transmission losses, thereby improving the performance of the proton exchange membrane water electrolysis hydrogen production membrane electrode and reducing the energy consumption of the electrolyzer.
[0021] (2) The present invention improves the preparation process of the catalyst layer so that the catalyst layer of the core component membrane electrode in the proton exchange membrane electrolyzer forms a layered structure, and by enhancing the conductive contact between the catalyst layer and the diffusion layer, and strengthening the precipitation and transmission of anode oxygen bubbles during water electrolysis, the performance of the membrane electrode for hydrogen production by proton exchange membrane water electrolysis is enhanced, the energy utilization efficiency during hydrogen production is improved, and the energy consumption of the electrolyzer using the membrane electrode is reduced. The problem that a dense ionomer layer that is non-conductive and hinders the transmission of electrolytic oxygen bubbles is formed on the surface of the anode catalyst layer of the membrane electrode during the preparation process of the membrane electrode for proton exchange membrane water electrolysis is solved.
[0022] (3) The membrane electrode preparation method of the present invention reduces the formation of a dense ionomer layer on the surface. The method is simple and low-cost. It only requires simple adjustments to the membrane electrode preparation process without the need to adopt new materials and processes. It can also significantly improve the performance of the membrane electrode for hydrogen production by electrolysis of water and improve the energy utilization efficiency of hydrogen production by electrolysis in the electrolytic cell.
[0023] (3) The method described in the present invention is applicable to the preparation of a proton exchange membrane water electrolysis hydrogen production electrolytic cell and a membrane electrode for a proton exchange membrane water electrolysis hydrogen production electrolytic cell, as well as other related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the basic structure of an existing proton exchange membrane water electrolysis cell;
[0025] Figure 2 It is a schematic diagram of the basic structure of membrane electrode;
[0026] Figure 3 Schematic diagram of the structure of the anode catalyst layer prepared in Example 1 and Comparative Examples 1-2, wherein a is the anode catalyst layer prepared by the spraying method in Comparative Example 1, b is the anode catalyst layer prepared by the hot pressing transfer method in Comparative Example 2, and c is the anode catalyst layer prepared in Example 1;
[0027] Figure 4 The schematic diagram of the structure of the anode catalyst layer of Comparative Example 2 under an electron microscope;
[0028] Figure 5 The schematic diagram of the structure of the anode catalyst layer of Comparative Example 1 under an electron microscope;
[0029] Figure 6 The electrode performance of the anode membrane electrode of Comparative Example 1-2, Spray in the figure represents the membrane electrode prepared by the spraying method, and HotPress represents the membrane electrode prepared by the hot pressing transfer method;
[0030] Figure 7 : It is the membrane electrode performance of Example 1 compared with that of Comparative Examples 1-2, wherein a is the electrolytic cell voltage of Example 1 and Comparative Examples 1-2 at different electrolysis current densities, b is the polarization performance loss (activation loss, ohmic loss and transmission loss) of Example 1 and Comparative Examples 1-2 at different electrolysis current densities, and in the figure, Spray represents the membrane electrode prepared by spraying, HotPress represents the membrane electrode prepared by hot pressing transfer, and Hierarchical represents the layered membrane electrode. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] The present invention relates to a novel proton exchange membrane water electrolysis hydrogen production membrane electrode with a layered catalytic layer structure, which is prepared by the following method:
[0033] S1, preparation of anode catalyst layer slurry: a catalyst (such as iridium dioxide or iridium black catalyst) and a perfluorosulfonic acid ionomer (such as ), a solvent (such as ethanol or isopropanol) in a mass ratio of 1: (0.1-1): (40-60), and then dispersed for 30 minutes using an ultrasonic dispersion method to obtain an anode catalyst layer slurry.
[0034] S2, preparation of Teflon hot-pressed sheet: 40-60% (preferably 50%) of the total weight of the prepared anode catalyst layer slurry is taken out as the slurry for hot-pressing the bottom dense layer. The amount of the slurry determines the thickness of the bottom dense layer of the membrane electrode, and the thickness of the bottom dense layer depends on the catalyst loading of the membrane electrode. The catalyst layer slurry is deposited on the Teflon film substrate by an ultrasonic sprayer or a doctor blade to prepare a Teflon hot-pressed sheet.
[0035] S3, hot pressing transfer method to prepare the bottom dense layer of the membrane electrode: cut the Teflon hot pressing sheet into the required size, cover it on the surface of the perfluorosulfonic acid proton exchange membrane, use a hot press to apply a pressure of 0.1-1MPa to it, the hot press temperature is 100℃-150℃, and the hot pressing is 1-10min. The pressure and temperature of the hot pressing are adjustable, both of which can be used to regulate the flatness and density of the bottom dense layer, where the hot pressing pressure and the hot press temperature are used to regulate the flatness and density of the bottom dense layer, and the flatness and density of the bottom dense layer depend on the catalyst loading of the membrane electrode.
[0036] After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0037] S4, spraying method to add an upper fluffy layer to the membrane electrode: use a sprayer to spray the remaining catalyst layer slurry that has not been taken by the hot pressing transfer method on the surface of the membrane electrode with a bottom dense catalyst layer obtained in step S3, the spraying pressure is 2-3bar, the nozzle working distance is 5-10cm, the spraying gas flow rate is 2-5L / min, and the spraying temperature is 80-100℃. The amount of slurry determines the thickness of the upper fluffy layer of the membrane electrode, and the thickness of the upper fluffy layer depends on the catalyst loading of the membrane electrode. After spraying, the anode catalyst layer of the membrane electrode with a layered structure is obtained.
[0038] S5, preparation of cathode catalyst layer slurry: a catalyst (such as a platinum catalyst) and a perfluorosulfonic acid ionomer (such as ), a solvent (such as ethanol or isopropanol) in a mass ratio of 1: (0.1-1): (40-60), and then dispersed for 30 minutes using an ultrasonic dispersion method to obtain a cathode catalyst layer slurry.
[0039] S6, preparing a cathode catalyst layer having a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4;
[0040] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0041] The raw materials and equipment used in the present invention are all conventional raw materials and equipment in the art, such as Accelerate, model Accelerate Ir Black; iridium dioxide is Shengernuo, catalyst model SIR85; iridium black catalyst is Accelerate, model Accelerate Ir Black. Perfluorosulfonic acid ionomer is commercially available Or other perfluorosulfonic acid ionomers.
[0042] Example 1
[0043] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0044] S1, iridium dioxide, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0045] S2, taking out 50% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0046] S3, cutting the Teflon hot-pressed sheet into a required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 0.5 MPa to it using a hot press, the hot press temperature is 120° C., and hot pressing is performed for 3 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0047] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 50% of the slurry not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0048] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0049] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0050] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0051] Figure 3 c shows the anode catalyst layer structure of the membrane electrode prepared in Example 1.
[0052] Comparative Example 1
[0053] The anode catalyst layer and the cathode catalyst layer are prepared by spraying, that is, the catalyst layer slurry prepared in step S1 of Example 1 is sprayed on the perfluorosulfonic acid proton exchange membrane by the spraying method of step S4. The rest is the same as in Example 1. Figure 3 a is a schematic diagram of the anode catalyst layer structure of the membrane electrode prepared in Comparative Example 1. Figure 5 The structure of the anode catalyst layer of the membrane electrode prepared in Comparative Example 1 under an electron microscope is shown, and it can be seen that its surface structure is fluffy.
[0054] Comparative Example 2
[0055] The anode catalyst layer and the cathode catalyst layer were prepared by hot pressing transfer method, that is, the catalyst layer slurry prepared in step S1 of Example 1 was completely transferred onto the perfluorosulfonic acid proton exchange membrane by the method of steps S2-S3. The rest was the same as in Example 1. Figure 3 b is a schematic diagram of the anode catalyst layer structure of the membrane electrode prepared in Comparative Example 2, Figure 4 The structure of the anode catalyst layer of the membrane electrode prepared in Comparative Example 2 under an electron microscope is shown, and it can be seen that its surface structure is flat and dense.
[0056] See also Figure 3 As can be seen from the figure, in Example 1, a dense and flat bottom catalyst layer is first obtained on the proton exchange membrane by hot pressing transfer, and then the slurry is sprayed thereon by spraying. In this way, the alcohol solvent in the slurry will not directly contact the proton exchange membrane during spraying to cause deformation of the membrane, and a loose and flat surface structure without a dense ionomer layer on the surface can be obtained. Example 1 solves the defects of the two methods of Comparative Examples 1-2.
[0057] The membrane electrode prepared in Example 1 and Comparative Examples 1-2 was assembled in an electrolytic cell for performance testing. The test method and conditions were as follows:
[0058] Test conditions: In an electrolytic cell with an active area of 2cm*2cm, using a water temperature of 80℃ and an anode water supply rate of 10ml / min, test IV curve (1~4A / cm 2 ) and use high frequency impedance test (HFR, test frequency 100KHz ~ 100Hz) to measure the ohmic resistance at various current densities.
[0059] From the IV curve and ohmic resistance, the voltage of the electrolytic cell can be broken down into the following voltages:
[0060] V 电解池 =V 可逆电压 +V 活化损失 +V 欧姆损失 +V 传输损失
[0061] Where V 可逆电压 is the reversible voltage for electrolysis of water. In engineering applications, 1.23V can be used directly as an approximation, and 1.23V will be used in subsequent calculations.
[0062] The activation loss is given by: V 活化损失=b*log10(i / i0)
[0063] Where b is the Tafel slope (V / dec) obtained by fitting the IV curve by subtracting the ohmic voltage drop in the 0-0.1A current density range of the IV curve. i0 is the apparent exchange current density, which is the intersection of the Tafel fitting curve and the x-axis.
[0064] The ohmic losses are obtained by measuring the ohmic resistance at each current density. The ohmic losses can be calculated using the following formula:
[0065] V 欧姆损失 = each current density * ohmic loss at each current density
[0066] The transmission loss is obtained as follows:
[0067] According to V 电解池 =V 可逆电压 +V 活化损失 +V 欧姆损失 +V 传输损失
[0068] The total cell voltage V at each current density 电解池 , minus the reversible voltage V under the response current 可逆电压 , activation loss V 活化损失 , Ohmic loss V 欧姆损失 , the transmission loss V under each current can be calculated 传输损失 .
[0069] The test results are as follows:
[0070] <![CDATA[1Acm -2 ]]> Example 1 Comparative Example 1 Comparative Example 2 Activation loss (mV) 310 315 320 Ohm loss (mV) 110 130 135 Transmission loss (mV) 30 33 32
[0071] <![CDATA[2Acm -2 ]]> Example 1 Comparative Example 1 Comparative Example 2 Activation loss (mV) 325 326 322 Ohm loss (mV) 211 223 231 Transmission loss (mV) 42 56 63
[0072] <![CDATA[3A cm -2 ]]> Example 1 Comparative Example 1 Comparative Example 2 Activation loss (mV) 337 339 334 Ohm loss (mV) 332 346 358 Transmission loss (mV) 53 135 157
[0073] <![CDATA[4A cm -2 ]]> Example 1 Comparative Example 1 Comparative Example 2 Activation loss (mV) 353 356 348 Ohm loss (mV) 425 451 463 Transmission loss (mV) 80 193 212
[0074] Combining from the above table Figure 6-7 It can be seen that after using the membrane electrode design of the present invention, the transmission loss of Example 1 increases much faster than that of Comparative Examples 1-2. At the same time, compared with Comparative Examples 1-2, the ohmic loss and transmission loss of Example 1 are both lower.
[0075] Figure 6The performance of the membrane electrode of Comparative Examples 1-2 is shown. It can be seen that due to the denser and smoother surface structure, the membrane electrode of Comparative Example 2 can provide better electron conduction, so the ohmic loss is lower. However, the dense and smooth surface structure of the membrane electrode of Comparative Example 2 also hinders the oxygen bubbles generated in the catalyst layer from being transmitted outward, thus causing greater transmission loss than the membrane electrode of Comparative Example 1.
[0076] Figure 7 The membrane electrode performance of Example 1 compared with Comparative Examples 1-2 is shown. Figure 7 As shown, it can be seen that the layered membrane electrode has better performance than the membrane electrode prepared by the hot pressing transfer method and the anode membrane electrode prepared by the spraying method. In the composition of polarization performance loss, it can be found that Example 1 has the lowest ohmic loss and transmission loss, which comes from the advantages of the catalyst layer structure obtained by both the hot pressing transfer method and the spraying method: the bottom dense layer ensures the overall flatness of the membrane electrode, and has excellent conductive contact with the titanium diffusion layer, reducing the ohmic loss. The fluffy layer on the surface provides a more efficient bubble transmission channel, which promptly removes the gas generated during electrolysis and reduces transmission losses.
[0077] The formation of a dense ionomer layer on the surface is reduced, which can significantly improve the performance of the membrane electrode for hydrogen production by electrolysis of water and improve the energy utilization efficiency of hydrogen production by electrolysis of the electrolyzer.
[0078] Example 2
[0079] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0080] S1, iridium dioxide, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0081] S2, taking out 40% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0082] S3, cutting the Teflon hot-pressed sheet into a required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 0.5 MPa to it using a hot press, the hot press temperature is 120° C., and hot pressing is performed for 3 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0083] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 60% of the slurry that is not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0084] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0085] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0086] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0087] Example 3
[0088] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0089] S1, iridium dioxide, and isopropanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0090] S2, taking out 50% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0091] S3, cutting the Teflon hot-pressed sheet into the required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 1 MPa to it using a hot press, the hot press temperature is 120°C, and hot pressing is performed for 3 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0092] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 50% of the slurry not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0093] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0094] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0095] S7, see Figure 2A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0096] Example 4
[0097] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0098] S1, iridium dioxide, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0099] S2, taking out 50% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0100] S3, cutting the Teflon hot-pressed sheet into the required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 0.5 MPa to it using a hot press, the hot press temperature is 150° C., and hot pressing is performed for 3 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0101] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 50% of the slurry not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0102] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0103] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0104] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0105] Example 5
[0106] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0107] S1, iridium dioxide, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0108] S2, taking out 50% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0109] S3, cutting the Teflon hot-pressed sheet into the required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 0.5 MPa to it using a hot press, the hot press temperature is 120°C, and hot pressing is performed for 10 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0110] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 50% of the slurry not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0111] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:0.3:50, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0112] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0113] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0114] Example 6
[0115] A proton exchange membrane water electrolysis hydrogen production membrane electrode having a layered catalytic layer structure, wherein the anode catalytic layer is prepared by the following method:
[0116] S1, iridium dioxide, and ethanol in a mass ratio of 1:1:60, and ultrasonically dispersed for 30 minutes to obtain a catalyst layer slurry.
[0117] S2, taking out 50% of the prepared catalyst layer slurry, and depositing it on a Teflon film substrate using an ultrasonic sprayer to prepare a Teflon hot-pressed sheet.
[0118] S3, cutting the Teflon hot-pressed sheet into a required size, covering it on the surface of the perfluorosulfonic acid proton exchange membrane, applying a pressure of 0.5 MPa to it using a hot press, the hot press temperature is 120° C., and hot pressing is performed for 3 minutes. After the hot pressing is completed, the Teflon film is removed to obtain a membrane electrode with a dense bottom catalytic layer.
[0119] S4, using a spraying method to add an upper fluffy layer to the membrane electrode: using a sprayer to spray the remaining 50% of the slurry not taken by the hot pressing transfer method, deposit it on the surface of the membrane electrode with the underlying dense catalytic layer to obtain the anode catalytic layer of the layered membrane electrode.
[0120] S5, preparation of cathode catalyst layer slurry: platinum catalyst, and ethanol in a mass ratio of 1:1:60, and ultrasonically dispersed for 30 minutes to obtain a cathode catalyst layer slurry.
[0121] S6, preparing a cathode catalyst layer with a layered structure on the other side of the membrane electrode obtained in step S4 using the cathode catalyst layer slurry obtained in step S5 according to steps S2-S4.
[0122] S7, see Figure 2 A titanium porous diffusion layer is set on both sides of the membrane electrode with anode and cathode catalyst layers obtained in step S6, and the membrane electrode is further assembled and applied to Figure 1 The proton exchange membrane water electrolysis cell shown.
[0123] The method of Example 1 was used to test the products obtained in Examples 2-6. The results are as follows:
[0124] The test results are as follows:
[0125] <![CDATA[4A cm -2 ]]> Example 2 Example 3 Example 4 Example 4 Example 5 Example 6 Activation loss (mV) 363 384 359 358 393 382 Ohm loss (mV) 423 435 431 434 441 439 Transmission loss (mV) 95 93 99 101 87 75
[0126] It can be seen from the above table that the products obtained in Examples 2-6 also have less ohmic loss and transmission loss.
[0127] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a membrane electrode for producing hydrogen by electrolysis of water, characterized in that: The method first transfers part of the catalyst layer slurry onto the proton exchange membrane by hot pressing to obtain a dense and flat bottom catalyst layer, and then sprays the remaining catalyst layer slurry thereon by spraying to obtain a layered structure membrane electrode.
2. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The catalyst layer slurry comprises a catalyst, a perfluorosulfonic acid ionomer and a solvent in a mass ratio of 1:(0.1-1):(40-60).
3. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 2, characterized in that: The catalyst layer slurry is obtained by mixing the catalyst, the perfluorosulfonic acid ionomer and the solvent and dispersing them ultrasonically.
4. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 3, characterized in that: The perfluorosulfonic acid ionomer is Or other perfluorosulfonic acid ionomers, the solvent is ethanol or isopropanol; An anode catalyst layer and a cathode catalyst layer with a layered structure are respectively arranged on both sides of the proton exchange membrane, wherein the catalyst used in the anode catalyst layer slurry is iridium dioxide or iridium black catalyst, and the catalyst used in the cathode catalyst layer slurry is platinum catalyst.
5. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The specific steps of the hot pressing transfer are: depositing the catalyst layer slurry on the substrate by ultrasonic spraying or scraping to obtain a hot pressed sheet, then covering the obtained hot pressed sheet on the surface of the proton exchange membrane, hot pressing, and then removing the substrate to obtain a membrane electrode with a dense bottom catalyst layer.
6. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 5, characterized in that: The substrate is a Teflon film substrate; the hot pressing pressure is 0.1-1MPa, the hot pressing temperature is 100°C-150°C, and the hot pressing time is 1-10min.
7. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The catalyst layer slurry is divided into two parts, one of which accounts for 40-60% of the total weight of the catalyst layer slurry and is transferred on the proton exchange membrane by hot pressing, and the remaining part is loaded on the surface of the catalyst layer obtained by hot pressing transfer by spraying.
8. A membrane electrode for producing hydrogen by electrolysis of water prepared by the preparation method according to any one of claims 1 to 7.
9. A membrane electrode for producing hydrogen by electrolysis of water according to claim 8, characterized in that: It comprises a proton exchange membrane, and an anode catalyst layer and a cathode catalyst layer arranged on both sides thereof. The anode catalyst layer and the cathode catalyst layer are both a dense and flat bottom catalyst layer and a porous and fluffy surface catalyst layer arranged in sequence on the surface of the proton exchange membrane.
10. The membrane electrode for producing hydrogen by electrolysis of water according to claim 9, characterized in that: The thickness of the bottom catalytic layer is 7 microns, the thickness of the surface catalytic layer is 3 microns, the porosity of the bottom catalytic layer is 40-60%, and the porosity of the surface catalytic layer is 60-80%.
Citation Information
Patent Citations
Preparation method of PEM water electrolysis hydrogen production low-iridium membrane electrode
CN115125549A
Asymmetric integrated membrane electrode and preparation method thereof
CN116936888A
Preparation process of hydrogen fuel battery membrane electrode
CN106784944A
Manufacturing method of membrane-electrode joined body
JP2002093424A
Catalyst transfer film and method of manufacturing the same as well as catalyst layer-electrolyte membrane laminate, membrane-electrode assembly, and solid polymer fuel cell manufactured with use of this transfer film
JP2011076907A